Dynamics of the execution of the investigative pedagogical practice process of deepening in educational scenarios in times of pandemic and post-pandemic. - Herrera Becerra, María Olga; Guerrero Fagua, Nelson (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Teacher training is oriented so that the teacher, through the reflection of his practice, recognizes the different contexts in which he lives and on which he carries out the educational work, from this scenario he becomes a mediator and trainer around his own pedagogical experience with the purpose of strengthening it and thus rethinking its theoretical, disciplinary and investigative development. This article presents reflections on the different work modalities of the Investigative and Deepening Pedagogical Practice (PPIP) of the Bachelor of Basic Education with an emphasis on Mathematics, Humanities and Spanish Language, carried out by Teachers in Training in their professional performance in some Educational Institutions as a challenge to be able to continue providing the educational service. In this sense, a theoretical foundation of the different work modalities that arose in the pedagogical practice is presented, on the other hand, the approach was enrolled from a qualitative research approach, which allows the analysis of three academic semesters corresponding to the years 2020 and 2021, through a survey of 582 teachers in training, the question related to the form of execution of the practice in each of the selected scenarios was taken as information. The analysis evidences the diversity of digital tools used in the development of the PPIP.